Effect of Vitamin E Tocotrienol and Its Combination with Ascorbic Acid to Types of Leukocytes White Rat (Rattus norvegicus L.) - Lestariningrum, Nur Auliani; Karwur, Ferry Fredy; Martosupono, Martanto (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2012)
Background: Immunity is not separated from the role of leukocytes with various types and functions. Tocotrienol is one of the vitamin E group of compounds with antioxidant properties which to play an important role in cell repair. The aims to determine how much of the effect of vitamin E tocotrienols and its combination with ascorbic acid on the types of leukocytes.Design and Method: Preparation of blood lear dosage edge is a technique used to determine the effect of treatment between types of leukocytes. The design of experiment was conducted with three treatment that feed intake vitamin E tocotrienols and ascorbic acid and their combination with the control and 3 repetitions. Quantitative data leukocyte counts obtained by calculating the percentage of each type of leukocytes in each treatment group and the mean of the data obtained compared with normal leukocyte counts. In addition, the data is processed by the leukocyte counts of variance test using a completely randomized design (CRD) and BNT level of 5% to determine the differences between treatments.Result: The administration of vitamin E tocotrienols and its combination with ascorbic acid influenced significantly (P> 0.05) to increase the neutrophil are 31.66% and 33.66%, 24.33% and 22.33% respectively, when compared with controls. On the other hand, there is a decrease in the percentage of lymphocytes are 26.66% and 29.16%, 19.50% and 17.00% respectively, when compared with controls. Vitamin E tocotrienols and combined with ascorbic acid did not give significant effect (P <0.05) the percentage of eosinophils, basophils and monocytes.Conclusion: The administration of vitamin E tocotrienols and its combination with ascorbic acid to give effect to the increase in neutrophils (Sains Medika, 4(1):46-56).